Antibodies against neuronal surface antigens in acute stroke: a systematic review and meta-analysis - Paolucci, Matteo; Zini, Andrea; Morelli, Luana; Liguori, Rocco; Giannoccaro, Maria Pia (Frontiers in Immunology, 2025)
BackgroundAntibodies against neuronal surface antigens (NSA-Abs), particularly against the NMDA receptor (NMDAR-Ab), have been reported in acute stroke patients (ASP). However, their role in stroke is far from being understood.MethodsWe conducted a systematic review and meta-analysis to investigate: 1) the frequency of NSA-Abs in patients with acute stroke compared to controls; 2) the de novo appearance of NSA-Abs after stroke; and 3) their effects on the clinical outcome.ResultsWe included nine studies in the qualitative analysis and seven in the quantitative analysis. Analyses were restricted to NMDAR-Abs due to the lack of data about other NSA-Abs. Considering only studies that adopted a cell-based assay, IgA-IgM NMDAR-Abs isotypes (but not the IgG) were found more frequently in patients with acute stroke (OR 2.69, 95% CI 2.00–3.62, I2 = 4%). There was no de novo NMDAR-Abs formation after stroke. There was no statistical difference in mean discharge/day–7 NIHSS (SMD 0.21, 95% CI -1.10–1.52, I2 = 84%) and 3–12-month mRS (SMD 0.38, 95% CI -0.56-1.32, I2 = 78%) between patients with stroke with and without NMDAR-Abs seropositivity.ConclusionsSerum IgA/IgM NMDAR-Abs are more frequent in patients with stroke than controls. Due to several methodological issues, these findings should be interpreted cautiously. Additional, methodologically robust studies are needed to clarify the prevalence and significance of NMDAR-Abs in patients with stroke.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022241278#:~:text=https%3A//www.crd.york.ac.uk/prospero/display_record.php%3FID%3DCRD42022241278, identifier CRD42022241278.